2011
DOI: 10.1111/j.1471-4159.2011.07300.x
|View full text |Cite
|
Sign up to set email alerts
|

rho1 GABAC receptors are expressed in fibrous and cartilaginous layers of chick sclera and located on sclera fibroblasts and chondrocytes

Abstract: rho 1 GABA C receptor antagonists inhibit myopia in chick but the site of this effect is not known. The sclera ultimately determines the shape and size of the globe and thus an untested possibility is that GABA agents have a scleral mechanism. Whether rho 1 GABA C receptors are expressed and located in chick sclera is unknown. Real-time PCR, western blot and immunohistochemistry were used to determine whether rho1 GABA C receptors are expressed and located in chick fibrous and cartilaginous sclera. Both layers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 49 publications
(129 reference statements)
2
16
0
Order By: Relevance
“…Animals and tissue were prepared as previously described [15]. Twenty-five 12-day-old White Leghorn cockerels ( Gallus gallus ) were obtained from Jinan Spafury Poultry Farms (Jinan, China).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Animals and tissue were prepared as previously described [15]. Twenty-five 12-day-old White Leghorn cockerels ( Gallus gallus ) were obtained from Jinan Spafury Poultry Farms (Jinan, China).…”
Section: Methodsmentioning
confidence: 99%
“…GABA A [6-8], GABA B [9-11], and GABA C [12] receptors have been reported in the retina. We have recently shown that rho 1 GABA C receptors are present in chick sclera [15]. A small number of cultured human corneal stem cells have been shown to exhibit GABA A receptor immunoreactivity [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that GABA receptors are located in chick ocular tissues, including the cornea, RPE, and cartilaginous and fibrous sclera, suggesting a potential role for GABA in mediating scleral remodeling (Cheng et al, 2011; Cheng et al, 2012; Cheng et al, 2013). Treatment of cultured chick scleral fibroblasts with GABA agonists resulted in scleral cell proliferation (as evidenced by increased DNA content in cell cultures), as well as a decrease in scleral GAG synthesis (Christian et al, 2014).…”
Section: Emmetropization and Scleral Remodelingmentioning
confidence: 99%
“…39 Earlier studies have shown antagonists to GABA receptors (GABA A , GABA A0r , and GABA B ) to inhibit myopia development whereas agonists increased myopia susceptibility in chicks. 40,41 In guinea pigs, the selective GABAc inhibitor, TPMPA, inhibits ocular growth and myopia (McFadden SA, et al IOVS 2011;52:ARVO E-Abstract 6306).…”
Section: Discussionmentioning
confidence: 99%